Developing an organizational culture that facilitates radical innovation in a mature small to medium sized company: emergent findings - McLaughlin, Patrick; Bessant, John; Smart, Palie (Cranfield University, 2005)
Existing theories in the broad field of innovation management suggest that organizational culture affects the propensity of firms to be innovative, in their new product development offerings. A major thrust of inquiry implies that mature firms often lose their propensity to be innovative, as some aspects of organisational culture that were previously associated with successful incremental change, become the current cultural inhibitors of radical innovation. Whilst a large proportion of the existing empirical research has concentrated on incremental innovation or innovation management in general, there is little known about the specific aspects of organisational culture that facilitate radical innovation. Furthermore, the literature tends to focus on ‘innovation stories’ in larger firms which often simply assume that smaller firms are more agile and therefore more innovative in their approach to value creation. This paper reports the results of an exploratory case study into specific aspects of an organisational culture within a R&D setting that enable radical product innovation, in a small to medium sized UK based company in the tobacco industry. A grounded research methodology and an action research approach utilised an “issue” focus to surface the presence and intensity of cultural attributes that enable and inhibit radical product innovation. This investigation identified nine emerging themes and key constructs of a “local” innovation culture that were found to influence radicalness in new product development ventures. The interrelationships between the themes are mapped and discussed in the context of current theoretical perspectives in the field of innovation management. Finally a conceptual framework incorporating two archetypal forms of innovation culture is outlined to articulate and scope the transition between these two “ideal” states.